Light-induced CoOX surface reconstruction in hollow heterostructure for durable photocatalytic seawater splitting - Chunyu Yuan; Hongfei Yin; Jing Li; Yuxi Zhang; Hongji Chen; Dongdong Xiao; Qizhao Wang; Yongzheng Zhang; Qi-Kun Xue (Nature Communications)
Abstract Photocorrosion triggered by the unconsumed photogenerated holes severely deteriorates the photocatalytic efficiency and stability of semiconductor photocatalysts, especially in seawater with complex ions. Here, we report a hierarchical hollow ZnIn2S4 heterostructure integrating an inner CoOx nanocage and atomically dispersed Pt anchoring at surface S vacancies for hydrogen evolution from natural seawater (23.88 mmol g−1 h−1) and pure water (48.99 mmol g−1 h−1) under visible light. The dynamic Co2+/Co3+ self-reconstruction of the inner CoOx cage effectively consumes photogenerated holes, while the outer Pt1 single atoms localized at S vacancies serve as electron sinks to facilitate electron extraction and proton reduction. Benefiting from the dynamic hole-scavenging mechanism via oxidation self-reconstruction, the Pt1-ZnIn2S4@CoOX photocatalyst exhibits enhanced durability against alkali metal ions in seawater and maintains high reactivity for long-term hydrogen evolution. This work underscores the importance of light-induced transition metal dynamic self-reconstruction within hierarchical hollow heterostructure photocatalysts for sustainable hydrogen evolution.